Gaya Belajar Peserta Didik dalam Pembelajaran Ips pada Kelas VII E Smpn 10 Pontianak - Sri Buwono; Oktapiani Risti; Thomy Sastra Atmaja; Aminuyati; Venny Karolina (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research was conducted to determine the learning styles of students in social studies learning in class VII E of SMPN 10 Pontianak. The research approach used is a qualitative approach with a case study method. Data collection techniques include observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. Based on the results of the research that has been carried out, it is clear that: 1. In implementing social studies learning, there are three stages carried out, namely a). Learning planning by creating learning tools that address students' learning styles, learning tools in the form of teaching modules, models, methods and media b). Implementation of learning with models, methods and learning media that are not commensurate with students' learning styles c). Learning evaluation includes formative and summative assessments 2. Learning styles of class students in learning in class VII E include: a). Visual learning style focuses on viewing image and video media b). Auditory learning style focuses on listening to lectures and discussions c). The kinesthetic learning style focuses on practice or moving using body movements as a guide. 3. Factors that influence students' learning styles are: a). Emotional b). Environment.